Intravascular Ultrasound in the Endovascular Treatment of Patients With Peripheral Arterial Disease: Current Role and Future Perspectives - Loffroy, Romaric; Falvo, Nicolas; Galland, Christophe; Fréchier, Léo; Ledan, Frédérik; Midulla, Marco; Chevallier, Olivier (Frontiers in Cardiovascular Medicine, 2020)
Over the last decade, intravascular ultrasound (IVUS) has emerged as a useful adjunctive tool to angiography in an increasing number of catheter-based procedures for peripheral arterial disease (PAD). IVUS catheters offer accurate cross-sectional imaging of arterial vessels with high dimensional accuracy and provide accurate information about lesion morphology. IVUS enables assessment of the plaque morphology, vessel diameter, and the presence of arterial dissections. Furthermore, IVUS is able to properly guide the best choice of appropriate percutaneous transluminal angioplasty (PTA) technique, guide the delivery of different devices, and assess the immediate result of any endovascular intervention. In the present review, the role of IVUS for PAD will be discussed, specifically the applications of IVUS technology during interventional procedures including PTA, stent sizing, crossing total occlusion, assessing residual narrowing and stent apposition and expansion, and atherectomy. Future perspectives of IVUS-guided treatments and cost-effectiveness of the systematic use of IVUS during endovascular interventions will be also discussed.